Amesuviridae: a new family of plant-infecting viruses in the phylum Cressdnaviricota, realm Monodnaviria - Herrera da Silva, João Paulo; Pereira de Resende, Franciely Maria; Ferreira da Silva, José Cleydson; De Breuil, Soledad; Nome Docampo, Claudia; Bejerman, Nicolas Esteban; Murilo Zerbini, Francisco (Springer, 2023)
The phylum Cressdnaviricota comprises viruses with single-stranded, circular DNA genomes that encode an HUH-type endonuclease (known as Rep). The phylum includes two classes, eight orders, and 11 families. Here, we report the creation of a twelfth family in the order Mulpavirales, class Arfiviricetes of the phylum Cressdnaviricota. The family Amesuviridae comprises viruses that infect plants and is divided into two genera: Temfrudevirus, including the species Temfrudevirus temperatum (with temperate fruit decay-associated virus as a member), and Yermavirus, including the species Yermavirus ilicis (with yerba mate-associated circular DNA virus as a member). Both viruses encode Rep proteins with HUH endonuclease and SH3 superfamily helicase domains. Phylogenetic analysis indicates that the replicative module of amesuviruses constitutes a well-supported monophyletic clade related to Rep proteins from viruses in the order Mulpavirales. Furthermore, both viruses encode a single capsid protein (CP) related to geminivirus CPs. Phylogenetic incongruence between the replicative and structural modules of amesuviruses suggests a chimeric origin resulting from remote recombination events between ancestral mulpavirales and geminivirids. The creation of the family Amesuviridae has been ratified by the International Committee on Taxonomy of Viruses (ICTV).